Analysis of the Effect of Debt Policy on the Financial Performance of Companies Food & Beverages Subsector Listed on IDX for the 2016-2021 Period - Dani, Bayu Alamsyah; Riyadi, Rizal (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
This research aims to determine the effect of debt policy on the financial performance of Food and Beverages companies listed on the Indonesia Stock Exchange. Debt policy is proxied by short term debt (STD), long term debt (LTD), and total debt (TD), while financial performance is proxied by return on equity (ROE). The period used in this research is 6 (six) years, namely 2016 - 2021. This research is a type of quantitative research, using descriptive research methods. The research population is all Food and Beverages companies listed on the Indonesia Stock Exchange for the 2016-2021 period. The sample obtained was based on a purposive sampling technique, and 12 companies were obtained. The data analysis technique used is multiple linear regression analysis, namely regression using the independent variables short term debt (STD), long term debt (LTD), and total debt (TD). Based on the results of data analysis, STD has no effect on ROE with a calculated t value of -1.619, and a significance value of 0.110. The LTD variable has a negative and significant effect on ROE with a calculated t value of -3.024, and a significance level of 0.004. The TD variable has no effect on ROE with a calculated t value of 1.403 and a significance value of 0.165. The F test value in this research on calculated F was 3.984 with a significance level of 0.011. The adjusted R2 value is 0.112, so that the STD, LTD and TD variables are able to influence the ROE variable by 11.2% and the remaining 88.8% is explained by other factors outside this research model.